KINERJA PANTI SOSIAL BINA WANITA “MELATI” PROVINSI KALIMANTAN SELATAN - Ade Hermawan; Widarto Widarto (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2021)
The "Melati" Women's Social Institution of South Kalimantan Province carries out social rehabilitation in the form of social guidance activities and skills guidance for socio-economic vulnerable women. The "Melati" Women's Social Institution of South Kalimantan Province has a fairly good performance in providing social guidance and skills guidance to women who are socio-economically vulnerable. All indicators used to measure the performance of social guidance and skills guidance carried out by the "Melati" Women's Social Institution of South Kalimantan Province, namely productivity, service quality and accountability, showed good performance results.